BRCA1 andBRCA2 mutation status and cancer family history of Danish women affected with multifocal or bilateral breast cancer at a young age. Issue 6 (1st June 2001) - Bergthorsson, J T; Ejlertsen, B; Olsen, J H; Borg, A; Nielsen, K V; Barkardottir, R B; Klausen, S; Mouridsen, H T; Winther, K; Fenger, K; Niebuhr, A; Harboe, T L; et al.
Abstract : INTRODUCTION: A small fraction of breast cancer is the result of germline mutations in the BRCA1 and BRCA2 cancer susceptibility genes. Mutation carriers frequently have a positive family history of breast and ovarian cancer, are often diagnosed at a young age, and may have a higher incidence of double or multiple primary breast tumours than breast cancer patients in general. OBJECTIVES: To estimate the prevalence and spectrum of BRCA1 and BRCA2 mutations in young Danish patients affected with bilateral or multifocal breast cancer and to determine the relationship of mutation status to family history of cancer. SUBJECTS: From the files of the Danish Breast Cancer Cooperative Group (DBCG), we selected 119 breast cancer patients diagnosed before the age of 46 years with either bilateral (n=59) or multifocal (n=61) disease. METHODS: DNA from the subjects was screened for BRCA1 and BRCA2 mutations using single strand conformation analysis (SSCA) and the protein truncation test (PTT). Observed and expected cancer incidence in first degree relatives of the patients was estimated using data from the Danish Cancer Registry. RESULTS: Twenty four mutation carriers were identified (20%), of whom 13 had a BRCA1 mutation and 11 carried a BRCA2 mutation. Two mutations in BRCA1 were found repeatedly in the material and accounted for seven of the 24 (29%) mutation carriers. The mutation frequency was about equal in patients with bilateral (22%) and multifocal breast cancer (18%). The incidence of breast and ovarian cancer was greatly increased in first degree relatives of BRCA1 and BRCA2 mutation carriers, but to a much lesser degree in relatives of non-carriers. An increased risk of cancer was also noted in brothers of non-carriers. CONCLUSIONS: A relatively broad spectrum of germline mutations was observed in BRCA1 and BRCA2 and most of the mutations are present in other populations. Our results indicate that a diagnosis of bilateral and multifocal breast cancer is predictive of BRCA1 and BRCA2 mutation status, particularly when combined with information on the patients' age at diagnosis and family history of breast/ovarian cancer.